ANALISIS SINYAL GANGGUAN PADA DATA ELEKTROMAGNETIK - Miftakhul Maulidina (Fakultas Teknik - Universitas Riau, 2022)
The research using the very low frequency electromagnetic is widely used in field exploration. This is emitted by a transmitter. The data recorded are inphase, quadrature, t-field, and tilt. Inphase is real number. Quadrature is an imaginary number. They are related to each other to present existing anomalies. Both of them are useful for determining the location of an area that has a higher or lower resistivity than the surrounding area. However, the results of data recording are mixed with disturbing signals from around the object. This study aims to analyze how much the disturbing signal in the electromagnetic data recorded in the field. After processing the three points of the object in the field, it is found that the disturbing signals can be reduced by taking some sinusoidal graph results that reflect the stability of the waveform and removing the signal in the form of an irregular graphic display.